Pengaruh Leaflet Terhadap Pengetahuan Pasien Tentang Dagusibu Obat Antibiotik di Puskesmas Sungai Ulin - Fitriah, Rahmayanti; Permatasari, Rr. Ghinaa; Ramadhani, Syahrizal; Sajidah, Ainun (JURNAL FARMASI GALENIKA, 2025)
The high use of antibiotics can trigger resistance. Currently, people often make mistakes in obtaining, using, storing and disposing of drugs properly.This is one of the consequences of the lack of accurate information and the very low level of public education. Providing education on the use of antibiotics is important so that patients get maximum drug effectiveness and prevent resistance. This study aims to determine the effect of leaflets on patient knowledge about DAGUSIBU (Get, Use, Store, Discard) antibiotics at Sungai Ulin Public Health Center, Banjarbaru City. The type of research used was a pre-experiment with a one group pretest–post test research design. Sampling used a purposive sampling technique on 87 respondents. The pretest was given before education and the posttest was given 2 weeks after education. From the research results, the average value of the patient's pretest knowledge was 65.99% and the posttest was 87.83%. The statistical test method used was the Wilcoxon Signed Rank Test with an Asymp. Sig 2 tailed result of 0.000. This shows a significance value of <0.05, which means that the alternative hypothesis is accepted, where there is a significant difference in knowledge between before and after the intervention was given through leaflet media.